Implementing key management system based on openPGP protocol(RFC 2440) [electronic resource] - M.Norazizi Sham Mohd Sayuti (2004)
Thesis (Sarjana Sains (Sains Komputer (Real Time Software Engineering)) - Universiti Teknologi Malaysia, 2004